A porous high-density aluminum-based composite material and a method for preparing the same

CN121467696BActive Publication Date: 2026-10-27AVIC BEIJING INST OF AERONAUTICAL MATERIALS +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511684518.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-17
Publication Date
2026-10-27
Estimated Expiration
2045-11-17

AI Technical Summary

Technical Problem

[0002]传统铸造铝基复合材料存在纳米增强相易团聚、致密性不足(孔隙率大于5%)及强度提升有限(抗拉强度<400MPa)等问题,尽管激光选区熔化(SLM)3D打印技术可以实现复杂结构成形,但现有工艺制备的铝合金普遍面临高强度与功能化空隙结构难以协同的挑战——提高致密性会牺牲孔隙功能性,而引入孔隙则显著弱化力学性能

Benefits of technology

[0059]本发明提供了一种铝基复合材料,所述铝基复合材料由核壳结构的纳米前驱体TiB2-Al-Mg和铝基材料粉末,经激光选区熔化处理后得到;所述核壳结构的纳米前驱体TiB2-Al-Mg包括:内核为TiB2纳米颗粒,包覆层为Al和Mg的复合层,其中Al和Mg以混合形式包覆在TiB2纳米颗粒表面。与现有技术相比,本发明特别设计了一种具有特定结构和组成的铝基复合材料,并提供了相应的具有特定步骤和工艺的制备方法。本发明提供的铝基复合材料,具有多功能一体化的特点,具有≥99.5%的高致密性以及5%~30%的可控孔隙率的协同优化,高致密基体保证力学性能,多级孔隙结构实现吸能/散热/渗透功能,实现高强度-多功能耦合。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides an aluminum-based composite material, which is obtained by laser selective melting treatment of a core-shell structure nano precursor TiB2-Al-Mg and aluminum-based material powder; the core-shell structure nano precursor TiB2-Al-Mg comprises: a TiB2 nanoparticle as an inner core, and a composite layer of Al and Mg as a coating layer, wherein the Al and Mg are in a mixed form and coated on the surface of the TiB2 nanoparticle. The application adopts a laser selective melting technology, realizes the synergistic construction of in-situ self-grown nano strengthening phase and three-level gradient pore structure by gradient laser energy regulation and combination of the core-shell structure nano precursor. The application adopts strength-porosity decoupling regulation: the nano phase is generated in-situ under extreme conditions of a molten pool, the limitation of increased porosity caused by traditional addition of reinforcing phase is broken, a high-density matrix guarantees mechanical properties, a multi-level pore structure realizes energy absorption / heat dissipation / permeation function, and high strength-multifunction coupling is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of porous aluminum-based composite material preparation technology, and relates to an aluminum-based composite material, its preparation method and application, and particularly to a porous high-density aluminum-based composite material and its preparation method. Background Technology

[0002] Traditional cast aluminum matrix composites suffer from problems such as easy agglomeration of nano-reinforcing phases, insufficient density (porosity greater than 5%), and limited strength improvement (tensile strength < 400 MPa). Although selective laser melting (SLM) 3D printing technology can achieve the forming of complex structures, aluminum alloys prepared by existing processes generally face the challenge of balancing high strength with functionalized porous structures—increasing density sacrifices the functionality of pores, while introducing pores significantly weakens mechanical properties.

[0003] Although some corresponding studies have made improvements, they have only broken through the limitations of traditional reinforcing phase addition in theory. They have not yet solved the core problems such as precise control of pore-density structure and stability control of nanophase in engineering applications, which have restricted the development of porous high-strength aluminum matrix composites.

[0004] Therefore, finding a more suitable way to solve the aforementioned technical problems of existing aluminum-based composite materials has become one of the focal points of attention for many forward-thinking researchers in this field. Summary of the Invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide an aluminum-based composite material, its preparation method, and its application, particularly a porous, highly dense aluminum-based composite material. The aluminum-based composite material designed in this invention achieves synergistic optimization of high density (≥99.5%) and controllable porosity (5%~30%) in the aluminum matrix. Moreover, the preparation method is simple, highly controllable, and stable, making it more suitable for large-scale production and application.

[0006] This invention provides an aluminum-based composite material, which is obtained by selective laser melting of a core-shell structured nano-precursor TiB2-Al-Mg and aluminum-based material powder.

[0007] The core-shell structured nano-precursor TiB2-Al-Mg comprises: a core of TiB2 nanoparticles and a coating layer of Al and Mg composite layer, wherein Al and Mg are coated on the surface of TiB2 nanoparticles in a mixed form.

[0008] Preferably, the aluminum-based material includes aluminum and / or aluminum alloys;

[0009] The particle size of the nano-precursor TiB2-Al-Mg is 50~200nm;

[0010] The aluminum-based composite material has a three-level gradient pore structure.

[0011] The nano-precursor TiB2-Al-Mg is specifically the nano-reinforced precursor TiB2-Al-Mg;

[0012] The aluminum-based composite material contains an Al3TiMg rod-shaped reinforcing phase and a metastable Al-Ti-B-Mg precipitate phase;

[0013] The aluminum-based composite material includes porous, highly dense aluminum-based nanocomposite materials.

[0014] This invention provides a method for preparing an aluminum-based composite material, comprising the following steps:

[0015] 1) Under vacuum conditions, aluminum powder, titanium powder, magnesium powder and TiB2 particles are mixed to obtain a powder mixture;

[0016] 2) Under vacuum conditions, the powder mixture obtained in the above steps is subjected to cold isostatic pressing to obtain a cold-pressed block of the powder composite.

[0017] 3) The powder composite obtained in the above steps is cold-pressed into a block, then hydrogenated and dehydrogenated, and then ground to obtain composite powder;

[0018] 4) After mixing the composite powder obtained in the above steps with the aluminum-based material powder again, the mixture is processed by laser selective melting 3D printing and then subjected to ultra-fast cooling to obtain a composite material with a multi-level gradient pore structure.

[0019] 5) The composite material with multi-level gradient pore structure obtained in the above steps is subjected to hot isostatic pressing to obtain an aluminum-based composite material.

[0020] Preferably, the particle size of the aluminum powder, titanium powder and magnesium powder is independently selected from 15~53μm;

[0021] The TiB2 particles include TiB2 nanoparticles;

[0022] The TiB2 particles have a particle size of 50~200nm;

[0023] The volume ratio of the aluminum powder to the titanium powder is (1~5):1;

[0024] The total volume ratio of aluminum powder and titanium powder to magnesium powder is (2~10):1.

[0025] Preferably, the volume ratio of the magnesium powder to the TiB2 particles is (1~10):1;

[0026] The specific steps of the mixing process include the following: under vacuum conditions, aluminum powder and titanium powder are mixed first, then magnesium powder is added and mixed with the mixture of aluminum powder and titanium powder, and finally TiB2 particles are added and mixed to obtain a powder mixture.

[0027] The pressure of the cold isostatic pressing is 50~100MPa;

[0028] The holding time for the cold isostatic pressing is 0.5~2h;

[0029] The density of the cold-pressed powder composite is ≤50%.

[0030] Preferably, an oxygen removal step is included before the hydrogenation dehydrogenation step;

[0031] In the hydrogenation and dehydrogenation process, the holding temperature is 200~300℃.

[0032] In the hydrogenation and dehydrogenation process, the hydrogen pressure is greater than or equal to 0.2 MPa.

[0033] In the hydrogenation and dehydrogenation process, the heat and pressure holding time is 1-2 hours.

[0034] In the hydrogenation dehydrogenation process, the dehydrogenation method includes continuously introducing an inert gas and discharging hydrogen gas.

[0035] In the aforementioned hydrogenation dehydrogenation, the dehydrogenation process takes 1-2 hours.

[0036] In the hydrogenation dehydrogenation process, the holding temperature for the dehydrogenation process is 200~300℃.

[0037] Preferably, the grinding method includes ball milling;

[0038] The particle size of the composite powder is 15~53μm;

[0039] The particle size of the aluminum-based material powder is 15~53μm;

[0040] The volume ratio of the composite powder to the aluminum-based material powder is (1~30):(99~70).

[0041] In the laser selective melting 3D printing, the porous area adopts a fractal filling path, and the dense area adopts high-speed cross scanning.

[0042] The laser power in the laser selective melting 3D printing is controlled by gradient.

[0043] The gradient control includes: 200~400W at the layer center and 100~250W at the pore boundary.

[0044] Preferably, the ultrafast cooling rate is greater than or equal to 10.6 K / s;

[0045] The multi-level gradient is a three-level gradient pore structure;

[0046] The three-level gradient pore structure specifically includes: macroscopic pore structure, mesoscopic pore structure and nanoscale pore structure;

[0047] The pore size of the macroscopic pore structure is 100μm~1mm;

[0048] The pore size of the mesoscale pore structure is 10~100μm;

[0049] The pore size of the nanoscale pore structure is less than or equal to 1 μm.

[0050] Preferably, during the ultrafast cooling process, TiB2-Al-Mg in the composite material decomposes, generating in situ Al3TiMg nanorod reinforcing phase and metastable Al-Ti-B-Mg precipitate phase;

[0051] The diameter of the Al3TiMg nanorods is less than or equal to 20 nm;

[0052] The temperature of the hot isostatic pressing is 620~680℃;

[0053] The pressure of the hot isostatic pressing is 100~150MPa;

[0054] The hot isostatic pressing time is 2-4 hours;

[0055] The process after hot isostatic pressing also includes an aging treatment step;

[0056] The aging treatment temperature is 175~195℃;

[0057] The time for the time-sensitive processing is 8 to 20 hours.

[0058] The present invention also provides the application of the aluminum-based composite material described in any one of the above technical solutions or the aluminum-based composite material prepared by the preparation method described in any one of the above technical solutions in improving the density and / or controllability of the porosity of aluminum-based composite materials.

[0059] This invention provides an aluminum-based composite material, which is obtained by selective laser melting (SLM) of a core-shell structured nano-precursor TiB2-Al-Mg and aluminum-based material powder. The core-shell structured nano-precursor TiB2-Al-Mg comprises a core of TiB2 nanoparticles and a coating layer of Al and Mg composites, wherein Al and Mg are coated on the surface of the TiB2 nanoparticles in a mixed form. Compared with existing technologies, this invention specifically designs an aluminum-based composite material with a specific structure and composition, and provides a corresponding preparation method with specific steps and processes. The aluminum-based composite material provided by this invention has multifunctional integrated characteristics, exhibiting synergistic optimization of high density (≥99.5%) and controllable porosity (5%~30%). The high-density matrix ensures mechanical properties, while the multi-level porous structure achieves energy absorption / heat dissipation / permeability functions, realizing a high-strength, multifunctional coupling.

[0060] The method for preparing aluminum-based composite materials provided by this invention employs laser selective melting technology for surface treatment. By combining gradient laser energy modulation with a core-shell structured nano-reinforcing precursor (TiB2-Al-Mg), in-situ self-generated nano-reinforcing phases and a three-level gradient pore structure are synergistically constructed. This invention integrates the core-shell reinforcing precursor, laser gradient modulation, and multi-level pore design into a unified whole, employing strength-porosity decoupling control: nano-phases are generated in-situ under extreme conditions in the molten pool, overcoming the limitations of increased porosity caused by traditional reinforcing phase additions; moreover, it integrates multiple functions: a highly dense matrix (>99.5%) ensures mechanical properties, while the multi-level pore structure achieves energy absorption / heat dissipation / permeability functions, realizing high-strength-multifunctional coupling; simultaneously, it is process-compatible: suitable for existing metal 3D printing equipment, requiring no complex post-processing.

[0061] Experimental results show that this invention achieves the controllable preparation of nanocomposite materials with synergistic optimization of high density of aluminum matrix (≥99.5%) and controllable porosity of 5%~30% by combining selective laser melting (SLM) 3D printing technology and powder metallurgy technology with in-situ nano-reinforcement and porous structure design. Detailed Implementation

[0062] To further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention and not for limiting the claims of the present invention.

[0063] There are no particular restrictions on the source of any raw materials used in this invention; they can be purchased from the market or prepared using conventional methods known to those skilled in the art.

[0064] There are no particular restrictions on the purity of any of the raw materials used in this invention. However, this invention preferably uses analytical grade or conventional purity used in the field of aluminum-based composite material preparation.

[0065] This invention provides an aluminum-based composite material, which is obtained by mixing a core-shell structured nano-precursor TiB2-Al-Mg with aluminum-based material powder and then subjecting it to selective laser melting.

[0066] The core-shell structured nano-precursor TiB2-Al-Mg comprises: a core of TiB2 nanoparticles and a coating layer of Al and Mg composite layer, wherein Al and Mg are coated on the surface of TiB2 nanoparticles in a mixed form.

[0067] In this invention, the particle size of the nano-precursor TiB2-Al-Mg is preferably 50~200nm, more preferably 80~170nm, and even more preferably 110~140nm.

[0068] In this invention, the aluminum-based material preferably includes aluminum and / or aluminum alloys, more preferably aluminum alloys. Specifically, it can include any one or more of the 1-7 series aluminum alloys, aluminum-silicon alloys (including silicon-aluminum-magnesium alloys), etc. For example, one or more of 6061, AlSi10Mg, 7075 and A356 aluminum alloys. It can also be a cast aluminum alloy or a wrought aluminum alloy.

[0069] In this invention, the particle size of the aluminum-based material powder is 15~53μm, more preferably 20~43μm, and even more preferably 30~33μm.

[0070] In this invention, the nano-precursor TiB2-Al-Mg is preferably the nano-reinforced precursor TiB2-Al-Mg.

[0071] In this invention, the aluminum-based composite material preferably has a three-level gradient pore structure.

[0072] In this invention, the aluminum-based composite material preferably contains an Al3TiMg rod-shaped reinforcing phase and a metastable Al-Ti-B-Mg precipitate phase;

[0073] In this invention, the aluminum-based composite material preferably includes a porous, highly dense aluminum-based nanocomposite material.

[0074] This invention provides a method for preparing an aluminum-based composite material, comprising the following steps:

[0075] 1) Under vacuum conditions, aluminum powder, titanium powder, magnesium powder and TiB2 particles are mixed to obtain a powder mixture;

[0076] 2) Under vacuum conditions, the powder mixture obtained in the above steps is subjected to cold isostatic pressing to obtain a cold-pressed block of the powder composite.

[0077] 3) The powder composite obtained in the above steps is cold-pressed into a block, then hydrogenated and dehydrogenated, and then ground to obtain composite powder;

[0078] 4) After mixing the composite powder obtained in the above steps with the aluminum-based material powder again, the mixture is processed by laser selective melting 3D printing and then subjected to ultra-fast cooling to obtain a composite material with a multi-level gradient pore structure.

[0079] 5) The composite material with multi-level gradient pore structure obtained in the above steps is subjected to hot isostatic pressing to obtain an aluminum-based composite material.

[0080] The present invention first mixes aluminum powder, titanium powder, magnesium powder and TiB2 particles under vacuum conditions to obtain a powder mixture, namely the nano precursor TiB2-Al-Mg.

[0081] In this invention, the particle size of the aluminum powder, titanium powder and magnesium powder is preferably selected from 15~53μm, more preferably 20~43μm, and even more preferably 30~33μm.

[0082] In this invention, the TiB2 particles preferably include TiB2 nanoparticles.

[0083] In this invention, the particle size of the TiB2 particles is preferably 50~200nm, more preferably 80~170nm, and even more preferably 110~140nm.

[0084] In this invention, the volume ratio of aluminum powder to titanium powder is preferably (1~5):1, but can be (1~4):1, (1~3):1, or (1~2):1. Specifically, it can be 1:1.

[0085] In this invention, the volume ratio of the total volume of aluminum powder and titanium powder to the volume of magnesium powder is preferably (2~10):1, can be (3~8):1, or can be (4~6):1. Specifically, it can be 4:1.

[0086] In this invention, the volume ratio of magnesium powder to TiB2 particles is preferably (1~10):1, can be (1.5~7):1, or can be (2~4):1. Specifically, it can be 2:1.

[0087] In this invention, the specific steps of the mixing preferably include the following process: under vacuum conditions, aluminum powder and titanium powder are first mixed, then magnesium powder is added and mixed with the mixture of aluminum powder and titanium powder, and finally TiB2 particles are added and mixed to obtain a powder mixture.

[0088] The present invention further describes the process of cold isostatic pressing the powder mixture obtained in the above steps under vacuum conditions to obtain a cold-pressed block of the powder composite.

[0089] In this invention, the pressure of the cold isostatic pressing is preferably 50~100MPa, more preferably 60~90MPa, and even more preferably 70~80MPa.

[0090] In this invention, the holding time of the cold isostatic pressing is preferably 0.5~2h, more preferably 0.8~1.7h, and even more preferably 1.1~1.4h.

[0091] In this invention, the density of the cold-pressed powder composite is preferably ≤50%, more preferably ≤45%, and even more preferably ≤40%.

[0092] The present invention then cold-presses the powder composite obtained in the above steps into a block, and then performs hydrogenation and dehydrogenation before grinding to obtain a composite powder.

[0093] In this invention, an oxygen removal step is preferably included before the hydrogenation and dehydrogenation step. Specifically, the oxygen removal temperature is preferably 250~350℃, more preferably 270~330℃, and even more preferably 290~310℃.

[0094] In this invention, the holding temperature of the hydrogenation process in the hydrogenation dehydrogenation is preferably 200~300℃, more preferably 220~280℃, and even more preferably 240~260℃.

[0095] In this invention, during the hydrogenation and dehydrogenation process, the hydrogen pressure is preferably greater than or equal to 0.2 MPa, more preferably greater than or equal to 0.3 MPa, and even more preferably greater than or equal to 0.4 MPa.

[0096] In this invention, the heat preservation and pressure holding time of the hydrogenation process in the hydrogenation dehydrogenation is preferably 1~2h, more preferably 1.2~1.8h, and even more preferably 1.4~1.6h.

[0097] In this invention, the dehydrogenation process preferably includes continuously introducing an inert gas and discharging hydrogen gas.

[0098] In this invention, the dehydrogenation process is preferably carried out for 1 to 2 hours, more preferably 1.2 to 1.8 hours, and even more preferably 1.4 to 1.6 hours.

[0099] In this invention, the holding temperature of the dehydrogenation process in the hydrogenation dehydrogenation is preferably 200~300℃, more preferably 220~280℃, and even more preferably 240~260℃.

[0100] In this invention, the grinding method preferably includes ball milling.

[0101] In this invention, the particle size of the composite powder is preferably 15~53μm, more preferably 20~43μm, and even more preferably 30~33μm.

[0102] The present invention then mixes the composite powder obtained in the above steps with aluminum-based material powder again, processes it using laser selective melting 3D printing, and then cools it through ultrafast cooling to obtain a composite material printed part with a multi-level gradient pore structure.

[0103] In this invention, the composite powder is preferably a reinforcing phase or reinforcing body powder of an aluminum-based composite material.

[0104] In this invention, the volume ratio of the composite powder to the aluminum-based material powder is preferably (1~30):(99~70), can be (5~25):(95~75), or (10~20):(90~80).

[0105] In this invention, in the laser selective melting 3D printing, the pore area preferably adopts a fractal filling path, and the dense area adopts high-speed cross scanning.

[0106] In this invention, the laser power of the laser selective melting 3D printing is preferably controlled by gradient.

[0107] In this invention, the gradient control preferably includes: 200~400W at the layer center and 100~250W at the pore boundary; more preferably, 240~360W at the layer center and 130~220W at the pore boundary; and even more preferably, 280~320W at the layer center and 160~1910W at the pore boundary.

[0108] In this invention, the cooling rate of the ultrafast cooling is preferably greater than or equal to 10. 6 K / s, more preferably greater than or equal to 5×10 6 K / s, more preferably greater than or equal to 10 7 K / s.

[0109] In this invention, the preferred number of levels of the multi-level gradient is a three-level gradient pore structure.

[0110] In this invention, the three-level gradient pore structure preferably includes: macroscopic pore structure, mesoscopic pore structure and nanoscale pore structure.

[0111] In this invention, the pore size of the macroscopic pore structure is preferably 100μm~1mm, more preferably 300μm~800μm, and even more preferably 500μm~600μm.

[0112] In this invention, the pore size of the mesoscale pore structure is preferably 10~100μm, more preferably 30~80μm, and even more preferably 50~60μm.

[0113] In this invention, the pore size of the nanoscale pore structure is preferably less than or equal to 1 μm, more preferably less than or equal to 0.9 μm, and even more preferably less than or equal to 0.8 μm.

[0114] In this invention, during the ultrafast cooling process, TiB2-Al-Mg in the composite material is preferably decomposed, and Al3TiMg nanorod reinforcing phase and metastable Al-Ti-B-Mg precipitate phase are generated in situ.

[0115] In this invention, the diameter of the Al3TiMg nanorods is preferably less than or equal to 20 nm, more preferably less than or equal to 18 nm, and even more preferably less than or equal to 16 nm.

[0116] Finally, the composite material with a multi-level gradient pore structure obtained in the above steps is subjected to hot isostatic pressing to obtain an aluminum-based composite material.

[0117] In this invention, the temperature of the hot isostatic pressing is preferably 620~680℃, more preferably 630~670℃, and even more preferably 640~660℃.

[0118] In this invention, the pressure of the hot isostatic pressing is preferably 100~150MPa, more preferably 110~140MPa, and even more preferably 120~130MPa.

[0119] In this invention, the hot isostatic pressing time is preferably 2 to 4 hours, more preferably 2.4 to 3.6 hours, and even more preferably 2.8 to 3.2 hours.

[0120] In this invention, after hot isostatic pressing, an aging treatment step is preferably included.

[0121] In this invention, the aging treatment temperature is preferably 175~195℃, more preferably 179~190℃, and even more preferably 184~185℃.

[0122] In this invention, the aging process is preferably 8 to 20 hours, more preferably 10 to 18 hours, and even more preferably 12 to 16 hours.

[0123] The present invention provides the application of aluminum-based composite materials or aluminum-based composite materials prepared by any of the above-described technical solutions or by any of the above-described preparation methods in improving the density and / or controllability of aluminum-based composite materials.

[0124] This invention aims to complete and refine the overall technical solution, better ensure the structure and composition of aluminum-based composite materials, and further improve the density and porosity controllability of aluminum-based composite materials. Specifically, the aforementioned porous, highly dense aluminum-based composite material, its preparation method, and its applications may include the following:

[0125] This invention provides a method for preparing porous, highly dense aluminum-based nanocomposite materials. It employs laser selective melting technology and combines gradient laser energy regulation with a core-shell structured nano-reinforcing precursor (TiB2-Al-Mg) to achieve the synergistic construction of in-situ self-generated nano-reinforcing phases and a three-level gradient pore structure.

[0126] Specifically, the nano precursor is a core-shell structure of TiB2 nanoparticles coated with Al and Mg layers, with a particle size of 50~200nm.

[0127] Specifically, the laser power employs a gradient control strategy in the dense region and the pore boundary region, while a fractal scanning path is used in the pore region.

[0128] Specifically, the post-processing includes a two-stage process of hot isostatic pressing and aging heat treatment.

[0129] Furthermore, the preparation method provided by the present invention may specifically include the following steps:

[0130] Step 1: Material Preparation

[0131] Prepare a certain amount of pure aluminum powder, pure titanium powder, pure magnesium powder and TiB2 nanoparticles, wherein the particle size of pure aluminum powder, pure titanium powder and pure magnesium powder is 15~53μm, the particle size of TiB2 nanoparticles is 50~200nm, the volume ratio of pure aluminum powder to pure titanium powder is 1:1, the volume ratio of the total of pure aluminum powder and pure titanium powder to pure magnesium powder is 4:1, and the volume ratio of pure magnesium powder to TiB2 nanoparticles is 2:1.

[0132] Step 2: Powder Mixing

[0133] In a vacuum environment, pure aluminum powder and pure titanium powder are first mixed, then pure magnesium powder is added and mixed with the mixture of pure aluminum powder and pure titanium powder. Finally, TiB2 nanoparticles are added and mixed to obtain a powder mixture.

[0134] Step 3: Cold isostatic pressing

[0135] The powder mixture is subjected to cold isostatic pressing in a vacuum environment at a pressure of 50-100 MPa for a holding time of 0.5-2 h to obtain a cold-pressed block of the powder composite. The density of the cold-pressed block of the powder composite is <50%.

[0136] Step 4: Hydrogenation and Dehydrogenation

[0137] The cold-pressed powder composite is placed in a vacuum pressure vessel. After the oxygen in the vacuum pressure vessel is exhausted, hydrogen is introduced and heated. When the pressure reaches 2 atmospheres and the temperature reaches 200~300℃, the pressure is maintained for 1~2 hours. Then the pressure is released, argon is circulated to exhaust the hydrogen, and the temperature is maintained for another 1~2 hours. At this time, the pure magnesium powder undergoes a hydrogenation and dehydrogenation reaction, and nanocrystalline boundaries are formed inside the powder particles.

[0138] Step 5: Ball milling

[0139] The cold-pressed block of the powder composite that has undergone hydrogenation and dehydrogenation is placed in a ball mill jar for ball milling and crushing, and finally the powder composite with a particle size of 15~53μm is screened out.

[0140] Step Six: Laser Selective Melting 3D Printing

[0141] The powder composite obtained in the above steps is uniformly mixed with aluminum-based material powder and then subjected to selective laser melting 3D printing.

[0142] Specifically, laser power gradient control: 200-400W (layer center), 100-250W (pore boundary); fractal filling path (e.g., Hilbert curve) is used in the pore region, and high-speed cross-scanning is used in the dense region; ultra-fast cooling of the molten pool (>10) is utilized. 6 K / s) induces the decomposition of TiB2-Al-Mg, generating Al3TiMg nanorods (diameter <20nm) and metastable Al-Ti-B-Mg precipitates in situ, achieving grain boundary pinning reinforcement. During the printing process, a three-level gradient pore structure is preset through the CAD model (macroscale (100μm~1mm): biomimetic honeycomb structure; mesoscale (10~100μm): micropores generated by laser energy modulation; nanoscale (<1μm): residual pores from in-situ reaction).

[0143] Step 7: Hot Isostatic Pressing

[0144] The laser selective melting 3D printed parts were subjected to hot isostatic pressing at 620℃~680℃+100MPa~150MPa+2h~4h to eliminate micropores, and then subjected to aging treatment at 175℃~195℃+8h~20h for synergistic strengthening.

[0145] The present invention provides a porous, highly dense aluminum-based composite material, its preparation method, and its applications. The aluminum-based composite material provided by the present invention features multifunctional integration, exhibiting ≥99.5% high density and synergistic optimization of controllable porosity of 5%~30%. The highly dense matrix ensures mechanical properties, while the multi-level pore structure achieves energy absorption / heat dissipation / permeability functions, realizing a high-strength, multifunctional coupling.

[0146] The method for preparing aluminum-based composite materials provided by this invention employs laser selective melting technology for surface treatment. By combining gradient laser energy modulation with a core-shell structured nano-reinforcing precursor (TiB2-Al-Mg), in-situ self-generated nano-reinforcing phases and a three-level gradient pore structure are synergistically constructed. This invention integrates the core-shell reinforcing precursor, laser gradient modulation, and multi-level pore design into a unified whole, employing strength-porosity decoupling control: the nano-phase is generated in-situ under extreme conditions in the molten pool, overcoming the limitation of increased porosity caused by traditional reinforcing phase additions; moreover, it is multifunctional: a highly dense matrix (>99.5%) ensures mechanical properties, while the multi-level pore structure achieves energy absorption / heat dissipation / permeability functions, realizing high-strength-multifunctional coupling; simultaneously, it is process-compatible: suitable for existing metal 3D printing equipment, requiring no complex post-processing.

[0147] Experimental results show that this invention, through selective laser melting (SLM) 3D printing technology and powder metallurgy technology, combined with in-situ nano-reinforcement and porous structure design, achieves the controllable preparation of nanocomposite materials with synergistic optimization of aluminum matrix density ≥99.5% and controllable porosity of 5%~30%. The Young's modulus can reach 98GPa, and the specific strength is ≥280kN•m / kg (more than twice that of traditional porous aluminum).

[0148] To further illustrate the present invention, the following detailed description of an aluminum-based composite material, its preparation method, and its application is provided in conjunction with embodiments. However, it should be understood that these embodiments are implemented under the premise of the technical solution of the present invention, and detailed implementation methods and specific operating procedures are given only to further illustrate the features and advantages of the present invention, and are not intended to limit the scope of the claims of the present invention. The scope of protection of the present invention is not limited to the following embodiments.

[0149] Example 1

[0150] 1. Raw materials and proportions

[0151] Aluminum-based powder: gas-atomized AlSi10Mg powder, with a particle size range of 15~53μm, accounting for 94.5% of the total volume.

[0152] Nano-reinforced precursor: Core-shell structured TiB2@Al-Mg powder, with TiB2 nanoparticles (80 nm in diameter) as the core and an Al-Mg alloy coating layer. The particle size ranges from 15 to 53 μm, and this precursor powder accounts for 5.5% of the total volume.

[0153] Element volume ratio: Al : Ti : Mg ≈ 90 : 3.5 : 6.5 (achieved by adjusting the ratio of enhanced precursors to aluminum matrix).

[0154] 2. Preparation process

[0155] Precursor preparation: Aluminum powder, magnesium powder and TiB2 nanoparticles were ball-milled under argon protection (ball-to-material ratio 10:1, rotation speed 350 rpm, time 4h) to form a core-shell structured TiB2@Al-Mg precursor by mechanical alloying.

[0156] Cold isostatic pressing: The above-mentioned core-shell structured TiB2@Al-Mg precursor powder was loaded into a flexible rubber mold, sealed, and then subjected to cold isostatic pressing at a pressure of 80 MPa for 1.5 hours. The compact density was approximately 48%.

[0157] Hydrogenation and dehydrogenation:

[0158] Oxygen removal: Place the cold-pressed block in a vacuum furnace and evacuate to 1×10⁻⁶. -3 Pa, heated to 300℃ and held for 0.5 hours to remove adsorbed oxygen and moisture from the surface.

[0159] Hydrogenation: High-purity hydrogen gas is introduced to a pressure of 0.5 MPa, and the mixture is kept at 250°C and pressure for 1.5 hours.

[0160] Dehydrogenation: The vacuum is re-evacuated and high-purity argon is continuously introduced as a carrier gas. The mixture is kept at 280°C for 1.5 hours to completely remove the hydrogen.

[0161] Ball milling: The cold-pressed block of the powder composite that has undergone hydrogenation and dehydrogenation is placed into a ball mill jar for ball milling and crushing, and finally the powder composite with a particle size of 15~53μm is screened out.

[0162] Powder mixing: The prepared powder composite and AlSi10Mg matrix powder are mixed in a V-type powder mixer for 6 hours to ensure uniformity.

[0163] 3D Printing: Printing was performed using an SLM (Surface Mount Technology) system. Key parameters: layer thickness 30 μm, scanning speed 1200 mm / s, substrate preheating 200℃. Laser power gradient control: 380W laser power in dense regions, 150W laser power in pore boundary regions. A Hilbert curve fractal scanning path was used in the pore region, while a striped high-speed cross-scan was used in the dense region.

[0164] Post-processing: The printed parts were directly subjected to hot isostatic pressing (HIP) at 630℃ / 120MPa / 2h. This was followed by T6 aging heat treatment at 175℃ / 10h.

[0165] 3. Performance and structural characterization

[0166] Density: 99.7% (determined by Archimedes' water displacement method).

[0167] Pore ​​structure: A three-level gradient pore structure was successfully constructed, including macroscopic honeycomb structure (pore size ~500μm), mesoscopic laser-controlled micropores (pore size ~30μm), and nanoscale in-situ pores (pore size ~200nm), with a total porosity of approximately 12%.

[0168] Microstructure: TEM observation shows that in-situ generated Al3TiMg nanorods are uniformly distributed in the matrix, with a diameter of about 15 nm and a length of 100-200 nm, and a large number of metastable Al-Ti-B-Mg precipitates are also present.

[0169] Mechanical properties: Room temperature tensile test showed a tensile strength of 655 MPa, a yield strength of 580 MPa, and an elongation of 8.5%.

[0170] Example 2

[0171] 1. Raw materials and proportions

[0172] Aluminum-based powder: 6061 aluminum alloy powder, accounting for 92% of the total volume.

[0173] Nano-reinforced precursor: core-shell structured TiB2@Al-Mg powder (preparation method as in Example 1), accounting for 8% of the total volume.

[0174] Elemental volume ratio: Al : Ti : Mg ≈ 88 : 5 : 7.

[0175] 2. Preparation process

[0176] The process is basically the same as in Example 1, with the main adjustment being the parameters to suit 6061 aluminum alloy:

[0177] SLM laser power: 350W in dense region, 180W in pore boundary region.

[0178] Hot isostatic pressing (HIP): 650℃ / 110MPa / 3h.

[0179] Aging treatment: 185℃ / 12h.

[0180] 3. Performance and structural characterization

[0181] Density: 99.5%.

[0182] Pore ​​structure: Total porosity is controlled at 18%, and the three-level gradient structure is complete.

[0183] Microstructure: Al3TiMg nanorods have a higher density and a diameter of about 10~18 nm.

[0184] Mechanical properties: tensile strength of 635 MPa, yield strength of 560 MPa, and elongation of 7.8%. This demonstrates the applicability of the method to different aluminum-based systems.

[0185] Comparative Example 1

[0186] 1. Raw materials and proportions

[0187] Aluminum-based powder: AlSi10Mg powder, the same as in Example 1, comprising 100%.

[0188] No nano-reinforced precursors (TiB2@Al-Mg) were added.

[0189] 2. Preparation process

[0190] The SLM printing process is exactly the same as in Example 1, using the same laser power gradient control and scanning strategy.

[0191] The post-processing only involves T6 aging (175℃ / 10h) and does not involve hot isostatic pressing (HIP) to simulate conventional 3D printing aluminum alloy processes.

[0192] 3. Performance and structural characterization

[0193] Density: 98.9%. It contains many irregular pores of varying sizes, especially metallurgical defects of 20-50 μm.

[0194] Pore ​​structure: Unable to form controllable gradient pores, pore distribution is disordered, total porosity is about 14%, but most of them are harmful defects.

[0195] Microstructure: It is mainly an Al-Si eutectic structure, with no obvious nanorod-like or precipitated phase reinforcement.

[0196] Mechanical properties: tensile strength is only 385 MPa, yield strength is 280 MPa, and elongation is 6.0%.

[0197] See Table 1, which is a performance comparison analysis of the embodiments and comparative examples of the present invention.

[0198] Table 1

[0199]

[0200] The foregoing has provided a detailed description of a porous, highly dense aluminum-based composite material, its preparation method, and its applications. Specific examples have been used to illustrate the principles and implementation methods of the invention. The descriptions of these embodiments are merely illustrative of the methods and core ideas of the invention, including the best mode, and are intended to enable any person skilled in the art to practice the invention, including manufacturing and using any device or system, and implementing any combined method. It should be noted that those skilled in the art can make various improvements and modifications to the invention without departing from its principles, and these improvements and modifications also fall within the scope of protection of the claims. The scope of protection of this patent is defined by the claims and may include other embodiments conceived by those skilled in the art. If these other embodiments have structural elements that are not different from the wording of the claims, or if they include equivalent structural elements that are not substantially different from the wording of the claims, then these other embodiments should also be included within the scope of the claims.

Claims

1. A method for preparing an aluminum-based composite material, characterized in that, Includes the following steps: 1) Under vacuum conditions, aluminum powder, titanium powder, magnesium powder and TiB2 particles are mixed to obtain a powder mixture; The particle sizes of the aluminum powder, titanium powder, and magnesium powder are each independently selected from 15 to 53 μm; The TiB2 particles include TiB2 nanoparticles; The TiB2 particles have a particle size of 50~200nm; The volume ratio of the aluminum powder to the titanium powder is (1~5):1; The total volume ratio of aluminum powder and titanium powder to magnesium powder is (2~10):1; The volume ratio of magnesium powder to TiB2 particles is (1~10):1; 2) Under vacuum conditions, the powder mixture obtained in step 1) above is subjected to cold isostatic pressing to obtain a cold-pressed block of the powder composite; 3) The powder composite block obtained in step 2) is cold-pressed and then hydrogenated and ground to obtain composite powder; 4) After mixing the composite powder obtained in step 3) and the aluminum-based material powder again, the mixture is processed by selective laser melting 3D printing and then cooled ultrafast to obtain a composite material with a multi-level gradient pore structure. 5) The composite material with multi-level gradient pore structure obtained in step 4) above is subjected to hot isostatic pressing to obtain an aluminum-based composite material.

2. The preparation method according to claim 1, characterized in that, The specific steps of mixing in step 1) include the following process: under vacuum conditions, aluminum powder and titanium powder are mixed first, then magnesium powder is added and mixed with the mixture of aluminum powder and titanium powder, and finally TiB2 particles are added and mixed to obtain a powder mixture.

3. The preparation method according to claim 2, characterized in that, The pressure of the cold isostatic pressing is 50~100MPa; The holding time for the cold isostatic pressing is 0.5~2h; The density of the cold-pressed powder composite is ≤50%.

4. The preparation method according to claim 1, characterized in that, The hydrogenation dehydrogenation step is preceded by an oxygen removal step; In the hydrogenation and dehydrogenation process, the holding temperature is 200~300℃. In the hydrogenation and dehydrogenation process, the hydrogen pressure is greater than or equal to 0.2 MPa. In the hydrogenation and dehydrogenation process, the holding time for heat and pressure is 1-2 hours.

5. The preparation method according to claim 1, characterized in that, In the hydrogenation dehydrogenation process, the dehydrogenation method includes continuously introducing an inert gas and discharging hydrogen gas. In the aforementioned hydrogenation dehydrogenation, the dehydrogenation process takes 1-2 hours. In the hydrogenation dehydrogenation process, the holding temperature for the dehydrogenation process is 200~300℃.

6. The preparation method according to claim 1, characterized in that, The grinding method includes ball milling; The particle size of the composite powder is 15~53μm; The particle size of the aluminum-based material powder is 15~53μm; The volume ratio of the composite powder to the aluminum-based material powder is (1~30):(99~70).

7. The preparation method according to claim 1, characterized in that, In the laser selective melting 3D printing, the porous area adopts a fractal filling path, and the dense area adopts high-speed cross scanning. The laser power in the laser selective melting 3D printing is controlled by gradient. The gradient control includes: 200~400W at the layer center, 100~250W at the pore region boundary, and a dense region at the layer center.

8. The preparation method according to claim 1, characterized in that, The ultrafast cooling rate is greater than or equal to 10. 6 K / s; The multi-level gradient pore structure is a three-level gradient pore structure; The three-level gradient pore structure specifically includes: macroscopic pore structure, mesoscopic pore structure and nanoscale pore structure; The pore size of the macroscopic pore structure is 100μm~1mm; The pore size of the mesoscale pore structure is 10~100μm; The pore size of the nanoscale pore structure is less than or equal to 1 μm.

9. The preparation method according to claim 1, characterized in that, During the ultrafast cooling process, TiB2-Al-Mg in the composite material decomposes, generating in situ Al3TiMg nanorod reinforcing phase and metastable Al-Ti-B-Mg precipitate phase; The diameter of the Al3TiMg nanorods is less than or equal to 20 nm; The temperature of the hot isostatic pressing is 620~680℃; The pressure of the hot isostatic pressing is 100~150MPa; The hot isostatic pressing time is 2-4 hours; The process after hot isostatic pressing also includes an aging treatment step; The aging treatment temperature is 175~195℃; The time for the time-sensitive processing is 8 to 20 hours.

Citation Information

Patent Citations

  • Compound titanium powder and titanium-based composite material and preparation methods thereof

    CN105234404A

  • Nickel-based alloy powder and preparation method and application thereof

    CN113618060A